THE IMPACT OF INFLUENCER LIVESTREAMING TOWARDS THE CHINESE YOUTH CONSUMER BEHAVIOR - BI , DR. CHUANCHEN; HU, MEIXIN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
With the advent of the digital age, influencer live-streaming commerce has gradually become a new consumption model in China, exerting a profound impact on the purchasing behavior of young consumers. This study aims to explore the specific effects of influencer live-streaming on the consumption behavior of Chinese youth, utilizing Grounded Theory, the Consumer Decision-Making Process Model, and the 4C Marketing Theory as analytical frameworks. Through methods such as literature review and in-depth interviews, this research identifies the key factors influencing young consumers' behavior and analyzes the roles these factors play at various stages of the consumer decision-making process. The results indicate that influencer live-streaming effectively drives changes in consumption behavior by enhancing consumers' awareness, information search, evaluation, and purchase decision-making processes. Furthermore, based on the 4C Marketing Theory, this study proposes marketing strategies targeting young consumers to meet their needs, reduce costs, improve convenience, and strengthen communication. In conclusion, this research not only provides theoretical support for understanding the impact of influencer live-streaming commerce on youth consumption behavior but also offers practical recommendations for businesses to develop effective marketing strategies.